Investigation of the Thermohydraulic Effects of Using Fin in Liquid Metal Cooled Mini-channel Heat Sinks for Microprocessors - Kalkan, Orhan (Fırat University, 2024)
The need for effective cooling of microprocessors, whose processing speed is increasing, is also increasing at the same rate. This increases the work on more effective cooling methods. Mini/micro-channel heat sinks cooled with liquid metals can provide effective cooling due to their high heat conductivity. In this study, the impact of using fins on the thermal resistance coefficient and the resulting pressure drop in a mini-channel heat sink cooled with Galinstan is investigated. As a result of the numerical analysis created by the arrangement of the fins in the channel in different configurations and consisting of a total of 70 different models, no significant thermal performance improvement is observed when the distance between the fins is less than 1.5 mm, but it has been determined that excessive pressure drop occurs. When the fin length is 0.3 mm and the distance between the fins is 1.5 mm, a thermal performance improvement of 15.9% was obtained in the minimum fluid inlet velocity condition compared to the case without fins. On the other hand, there was an increase in pressure loss of 95 kPa in this case.

İşlem hızı giderek artan mikro işlemcilerin etkin soğutmaya olan ihtiyaçları da aynı ölçüde artış göstermektedir. Bu ise daha etkili soğutma yöntemleri üzerinde çalışmaları artırmaktadır. Sıvı metaller ile soğutulan mini/mikro kanallı soğutucular, yüksek ısı iletim katsayıları nedeni ile etkin soğutma sağlayabilmektedirler. Bu çalışmada, Galinstan ile soğutulan bir mini kanallı soğutucuda, kanatçık kullanımının ısıl direnç katsayısına ve oluşan basınç kaybına etkileri incelenmiştir. Kanatçıkların farklı konfigürasyonlarda kanal içinde yerleşimi ile oluşturulan ve toplamda 70 farklı modelden oluşan sayısal analiz sonucunda; kanatçıklar arası mesafenin 1,5 mm altında olması durumunda kayda değer bir ısıl performans iyileşmesi gözlemlenmemekle birlikte aşırı basınç kaybı oluşturduğu belirlenmiştir. Kanatçık boyunun 0,3 mm ve kanatçıklar arası mesafenin 1,5 mm olduğu durumda, kanatçıksız duruma göre minimum akışkan giriş hızı koşulunda %15,9 oranında ısıl performans iyileşmesi elde edilmiştir. Diğer yandan ise bu durumda 95 kPa değerinde basınç kaybı artışı yaşanmıştır.
Mikro İşlemciler için Sıvı Metal Soğutmalı Mini Kanallı Soğutucularda Kanatçık Kullanımının Termohidrolik Etkilerinin İncelenmesi
Keywords: Energy; Enerji; Numerical Methods in Mechanical Engineering; Makine Mühendisliğinde Sayısal Yöntemler